Acknowledgment to JCMK Editorial Board and Peer-Reviewers for contribution in 2024 - Yekaterina Dotsenko (Ķazaķstannyṇ Klinikalyķ Medicinasy)
The publication summarizes the results of the activities for the Journal of Clinical Medicine of Kazakhstan in 2024. It was prepared on behalf of the editorial team of the Journal to express appreciation to all editorial and advisory board members, reviewers and authors who contributed to this journal throuout the year.